Cover Jurnal Kebijakan dan Pegembangan Pendidikan Vol.3, No.1, Januari 2015 - ., Cover (Program Studi Magister Pedagogi, 2015)
Cover Jurnal Kebijakan dan Pegembangan Pendidikan Vol.3, No.1, Januari 2015